THE PERCEPTION OF SOCIETY ON JUDICIAL CANING AS THE FORM IMPLEMENTATION OF QANUN JINAYAH (PSYCHOLOGICAL PERSPECTIVE) - Nurbaiti Nurbaiti; Haiyun Nisa (Department of Islamic Psychology, The State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, Indonesia, 2021)
The implementation of a rule and form of punishment to create a safe and prosperous society will have an effect and impact on the fabric of social life. The implementation of judicial caning stipulated in the Qanun Jinayah has gained diverse views from society. The purpose of this study was to determine how society's perceptions of the implementation of judicial caning. This study used a qualitative method with observation and focus group techniques. A total of 31 people from 3 (three) regions in Banda Aceh City were selected as research respondents using purposive sampling techniques. The results point out that the perceptions that arise from the society are influenced by knowledge and views on judicial caning and its implementation as well as the psychosocial conditions of the society. Society does not quite understand the nature of Jinayah law, the purpose of punishment, and the order as well as the law to be realized. On the other hand, society also considers that judicial caning can provide a deterrent effect and learning to the society so that it does not violate the Sharia law.